Modeling Of Dynamic Behavior In Closed Crack And Nonlinear Ultrasonic Array Imaging - Ibrahim, Asriana (2017)
Ultrasonic testing (UT) utilizes the traveling time and amplitude of a scattered wave from cracks in a material. A distinct scattered wave can be obtained from a crack with opening faces. It is difficult, by contrast, to detect signals from closed cracks such as stress corrosion and fatigue cracks using the conventional UT. Since the crack faces are in contact due to a residual stress, most of the incident wave penetrates the crack faces and a little scattered wave will be generated. A nonlinear ultrasonic method based on contact acoustic nonlinearity (CAN) which utilizes the dynamic behaviors of the contact and separation states of the crack faces is a promising method. The clapping motion of the crack faces generates harmonics in the frequency spectrum. However, the generation of the harmonics from the crack faces is so sensitive that the voltage, angle, cycle, and frequency of the incident wave should be set in a well-chosen method.In this thesis, a modeling of the generation of the harmonics wave from the closed crack was performed to enhance the reliability of the nonlinear ultrasonic method. Here, an elastodynamic finite integration technique (EFIT) was introduced to simulate a transient motion of the scattered wave from the closed crack. The EFIT adopted a set of split computational nodes at the interface of the closed crack to show the contact and separation depending on the stress and opening displacement of the interface. The numerical results for one-dimensional wave field showed good agreement with the analytical solutions. The simulation results revealed that a closing velocity of the interface was determined by the compressive pressure of the material and was validated by the experimental measurement with polymethylmethacrylate (PMMA) specimens. The appropriate conditions to obtain the nonlinear ultrasonic wave in the case of ultrasonic array testing were determined by performing two-dimensional simulations.An imaging method of the closed crack using an array transducer was investigated using the EFIT simulation. The full waveforms sampling and processing (FSAP) was applied as the imaging technique. For the generation of the nonlinear ultrasonic wave from the closed crack, the FSAP was modified to an algorithm which can transmit a strong beam from the array transducer by setting the delay for all elements electronically. The second harmonic component which extracted from the scattered wave using a band-pass filter was used as the input to the FSAP imaging technique. From the results, it was found that the shape and the location of the closed crack can be reconstructed when the amplitude, frequency, cycle, and angle of the incident wave are set at appropriate values.